The Reflect of the Mystical Sincerity in the Kashani and Lahiji Poems - Elahinejad, M. R.; Rahimi, A. (Opción, 2019)
In the present research, the mystical concept of sincerity has been analyzed, based on the poetries of Faiz Kashani’s and Fayyaz Lahidji’s, in the form of seven main sections through a comprehensive review and comparison methodology. The results from each section indicated the extent to which Feyz and Fayyaz are influenced by each other’s thoughts and explain the facets of their sharing and differentiation. As a conclusion, succession results may be in the form of getting to the position of the right to receive, the reward of goodness, the illumination of life, peace and prosperity and etc.